English

Differentiate Each of the Following from First Principle: E √ 2 X - Mathematics

Advertisements
Advertisements

Question

Differentiate each  of the following from first principle:

\[e^\sqrt{2x}\]

Solution

\[ \frac{d}{dx}\left( f(x) \right) = \lim_{h \to 0} \frac{f\left( x + h \right) - f\left( x \right)}{h}\]
\[\frac{d}{dx}\left( e^\sqrt{2x} \right) = \lim_{h \to 0} \frac{e^\sqrt{2(x + h)} - e^\sqrt{2x}}{h}\]
\[ = 2 \lim_{h \to 0} \frac{e^\sqrt{2x + 2h} - e^\sqrt{2x}}{2x + 2h - 2x}\]
\[ = 2 \lim_{h \to 0} \frac{e^\sqrt{2x} \left( e^\sqrt{2x + 2h} - \sqrt{2x} - 1 \right)}{\left( \sqrt{2x + 2h} \right)^2 - \left( \sqrt{2x} \right)^2}\]
\[ = 2 e^\sqrt{2x} \lim_{h \to 0} \frac{e^\sqrt{2x + 2h} - \sqrt{2x} - 1}{\left( \sqrt{2x + 2h} - \sqrt{2x} \right)\left( \sqrt{2x + 2h} + \sqrt{2x} \right)}\]
\[ = 2 e^\sqrt{2x} \lim_{h \to 0} \frac{e^\sqrt{2x + 2h} - \sqrt{2x} - 1}{\left( \sqrt{2x + 2h} - \sqrt{2x} \right)} \lim_{h \to 0} \frac{1}{\left( \sqrt{2x + 2h} + \sqrt{2x} \right)}\]
\[ = 2 e^\sqrt{2x} \left( 1 \right)\frac{1}{2\sqrt{2x}}\]
\[ = \frac{e^\sqrt{2x}}{\sqrt{2x}}\]

 

shaalaa.com
  Is there an error in this question or solution?
Chapter 30: Derivatives - Exercise 30.2 [Page 26]

APPEARS IN

RD Sharma Mathematics [English] Class 11
Chapter 30 Derivatives
Exercise 30.2 | Q 3.09 | Page 26

Video TutorialsVIEW ALL [1]

RELATED QUESTIONS

Find the derivative of x–4 (3 – 4x–5).


Find the derivative of the following function (it is to be understood that a, b, c, d, p, q, r and s are fixed non-zero constants and m and n are integers):

(ax + b)n (cx + d)m


Find the derivative of the following function at the indicated point: 

 sin x at x =\[\frac{\pi}{2}\]

 


Find the derivative of the following function at the indicated point:


\[\frac{2}{x}\]


\[\frac{x^2 - 1}{x}\]


\[\frac{x + 1}{x + 2}\]


 x2 + x + 3


Differentiate  of the following from first principle:

e3x


Differentiate  of the following from first principle:

\[\cos\left( x - \frac{\pi}{8} \right)\]


Differentiate of the following from first principle:

 x cos x


Differentiate each of the following from first principle:

x2 e


\[\sin \sqrt{2x}\]


 log3 x + 3 loge x + 2 tan x


\[\frac{1}{\sin x} + 2^{x + 3} + \frac{4}{\log_x 3}\] 


If for f (x) = λ x2 + μ x + 12, f' (4) = 15 and f' (2) = 11, then find λ and μ. 


x3 sin 


xn tan 


x5 ex + x6 log 


x−3 (5 + 3x


\[\frac{2x - 1}{x^2 + 1}\] 


\[\frac{e^x - \tan x}{\cot x - x^n}\] 


\[\frac{x \tan x}{\sec x + \tan x}\]


\[\frac{2^x \cot x}{\sqrt{x}}\] 


\[\frac{x^2 - x + 1}{x^2 + x + 1}\] 


\[\frac{\sqrt{a} + \sqrt{x}}{\sqrt{a} - \sqrt{x}}\] 


\[\frac{1 + \log x}{1 - \log x}\] 


\[\frac{x^5 - \cos x}{\sin x}\] 


\[\frac{1}{a x^2 + bx + c}\] 


If x < 2, then write the value of \[\frac{d}{dx}(\sqrt{x^2 - 4x + 4)}\] 


If f (1) = 1, f' (1) = 2, then write the value of \[\lim_{x \to 1} \frac{\sqrt{f (x)} - 1}{\sqrt{x} - 1}\] 


If f (x) =  \[\log_{x_2}\]write the value of f' (x). 


Mark the correct alternative in  of the following:

If\[f\left( x \right) = 1 - x + x^2 - x^3 + . . . - x^{99} + x^{100}\]then \[f'\left( 1 \right)\] 


Mark the correct alternative in  of the following:
If\[f\left( x \right) = 1 + x + \frac{x^2}{2} + . . . + \frac{x^{100}}{100}\] then \[f'\left( 1 \right)\] is equal to 


Find the derivative of 2x4 + x.


Find the derivative of f(x) = tan(ax + b), by first principle.


Let f(x) = x – [x]; ∈ R, then f'`(1/2)` is ______.


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×